2016
DOI: 10.1007/s10751-016-1241-5
|View full text |Cite
|
Sign up to set email alerts
|

Spin canting in ferrite nanoparticles

Abstract: Recently, an easily scalable process for the production of small (3−7 nm) monodisperse superparamagnetic ferrite nanoparticles MeFe 2 O 4 (Me = Zn, Mn, Co) from iron metal and octanoic acid has been reported (Salih et al., Chem. Mater. 25 1430-1435 2013). Here we present a Mössbauer spectroscopic study of these ferrite nanoparticles in external magnetic fields of up to B = 5 T at liquid helium temperatures. Our analysis shows that all three systems show a comparable inversion degree and the cationic distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When the temperature is raised to reflux at 300 °C, magnetite cores nucleate and grow first, followed by growth of the Mn ferrite shells. In some cases core/shell NPs have been prepared by design with a two-stage process 8,13,27 , while in other some cases the differential decomposition may have unintentionally generated core/shell NPs 20,28,29 .
Figure 2( a ) HAADF-STEM images of nanoparticles showing spinel structure in magnetite cores. ( b ) integrated map of the Mn L 2,3 EELS signal, where green intensity shows the Mn distribution.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the temperature is raised to reflux at 300 °C, magnetite cores nucleate and grow first, followed by growth of the Mn ferrite shells. In some cases core/shell NPs have been prepared by design with a two-stage process 8,13,27 , while in other some cases the differential decomposition may have unintentionally generated core/shell NPs 20,28,29 .
Figure 2( a ) HAADF-STEM images of nanoparticles showing spinel structure in magnetite cores. ( b ) integrated map of the Mn L 2,3 EELS signal, where green intensity shows the Mn distribution.
…”
Section: Resultsmentioning
confidence: 99%
“…Since then numerous studies of ferrite NPs have identified a separate component in Mössbauer spectra attributed to canted spins 1720 , or to disordered surface spins 21 . Small angle neutron scattering demonstrated spin canting that was coherent within a surface shell for Fe 3 O 4 NPs 7 ; this has been confirmed by a combination of high resolution electron energy loss spectroscopy (HREELS) and density functional theory (DFT) calculations 9 .…”
Section: Introductionmentioning
confidence: 99%
“…5, a, with effective fields less than the fields of iron ions in (A)and [B]-positions and with lines considerably wider than those of other sixtuplets. It should be noted, that similar MS with sixtuplet lines asymmetric toward the zero speed were observed, for example, in [30,35,40,45,68,[79][80][81][82][83][84][92][93][94][95], however this fact was left unexplained.…”
Section: öSsbauer Studies Of Co 1−x Zn X Fe 2 O 4 Mnpsmentioning
confidence: 81%
“…Surface spin disorder as a result of symmetry breaking in the crystal structure at the NP surface and altered exchange interactions lead to canted spins and a reduction in magnetic moment of the NP . In general, surface spins are more susceptible to spin canting than interior moments, and such canting has been observed experimentally in many ferrites and iron oxides NPs. The degree of canting is influenced by anisotropy, intraparticle effects due to Dzyaloshinskii–Moriya interactions and NP size allowing for possible ways to tailor spin disorder in core–shell NPs through careful selection of constituent materials and synthesis parameters.…”
Section: Introductionmentioning
confidence: 99%